Coolie chains: global commodities, colonialism and the question of labour - Tappe, Oliver (DIE ERDE – Journal of the Geographical Society of Berlin, 2016)
The analysis of global commodity chains calls for a close attention to the question of labour – in colonial times as well as in the present. Since the economy of the French domains in Indochina and New Caledonia relied on labour-intensive resource extraction (rubber, minerals), the colonial administration and French enterprises envisaged a system of coolie labour that implied the transfer of thousands of Vietnamese labourers from densely populated Tonkin to the newly established plantations and mines. The emergence of global commodity chains linked to European industrialization in the 19th and early 20th century thus entailed considerable social transformations in the colonies as a result of changing labour regimes.